Lord Sebastian's secret - Ashford, Jane (Ashford, Jane. Duke's sons, 2017)
Lord Sebastian Gresham is a battle-tested soldier and brilliant strategist. Yet all his life he's had to hide his complete failure to decipher letters. In his own mind, he's just stupid. What a miracle it is that he's found the perfect bride. Lady Georgina Stane is beautiful, witty, and brilliantly intelligent. Sebastian is head over heels in love, proud as a peacock, and terrified. If she finds out, he'll lose her love forever.